2013
DOI: 10.1002/lary.24407
|View full text |Cite
|
Sign up to set email alerts
|

CD34‐positive fibroblasts in Reinke's edema

Abstract: Objectives/Hypothesis: To elucidate whether and to what extent CD341 fibroblasts (so-called CD341 fibrocytes, CD341 dendritic cells, and CD341 stromal cells) occur in normal human vocal folds and in Reinke's edema.Study Design: Histological study. Methods: Conventional, immunohistochemical, and ultrastructural procedures were performed in histological blocks of 18 selected cases of Reinke's edema (with typical findings including acellular edematous spaces in the subepithelial connective tissue of vocal folds, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
10
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 64 publications
(134 reference statements)
0
10
0
1
Order By: Relevance
“…Hyperplasia of CD34-immunoreactive ICs has been previously described being associated with inflammation and tumoral processes and in myxoid and edematous lesions [2123]. In many of these cases, IC proliferation is accompanied by acquisition of a voluminous nucleus and cytoplasm, with wider and shorter prolongations [22, 24]. Together these changes suggest IC activation by inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…Hyperplasia of CD34-immunoreactive ICs has been previously described being associated with inflammation and tumoral processes and in myxoid and edematous lesions [2123]. In many of these cases, IC proliferation is accompanied by acquisition of a voluminous nucleus and cytoplasm, with wider and shorter prolongations [22, 24]. Together these changes suggest IC activation by inflammation.…”
Section: Discussionmentioning
confidence: 91%
“…These voluminous cells of increased somatic size show some retracted processes and resemble modified CD34+SCs/TCs in the plexiform type of neurofibroma, in which myxoid deposits can be prominent [ 32 ]. Myxoid lagoons are partially or totally covered by CD34+SCs/TCs ( Figure 5 A–C), as occurs around spaces with abundant extracellular glycosaminoglycans (hyaluronic acid) [ 63 ].…”
Section: Cd34+scs In Non-tumoral Pathological Skinmentioning
confidence: 99%
“…In Reinke's edema, the production of collagen fibers would be altered as a result of toxic chemical mediators found in cigarettes. Días-Flores et al, 20 in a study on immunohistochemistry, observed an increase in density and morphological abnormalities in the population of fibroblasts in the lamina propria of Reinke's edema. These cells are arranged in a myxoid stroma, along with macrophages, and present positive immunoexpression for vimentin, CD34, and CD10, markers for hematopoietic cells, and, to a lesser extent, CD99, marker of mesenchymal tumors.…”
Section: E12mentioning
confidence: 96%